SISTEM PENGENDALIAN INTERNAL MONITORING INVENTORY OBAT MENGGUNAKAN SUPPLY CHAIN MANAGEMENT - Adhie Thyo Priandika (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
Purna Husada is a pharmacy that provides various kinds of medicines, internal control procedures and inventory monitoring are carried out using only goods notes and stock cards, the process of requesting goods carried out by the company still uses telephone media by providing data on drugs to be ordered and stock of goods to be ordered. still being processed in the notebook and the importance of the need for medicine for consumers must be met. Supply Chain Management is a process in which the flow of raw materials, information, and inter-company finance occurs in order to fulfill consumer orders. The process carried out to meet the supply of raw materials starts from retail demand by distributors and consumer demand by retail, a good supply chain process can meet a stable supply with the aim of no shortage of raw materials or finished materials. Supply chain management is carried out to improve the supply process carried out by suppliers, manufacturers, distributors, retailers, and customers, this concept is a multi-layer supply chain consisting of final materials that have many products that are ready to sell. This process still has problems such as instability of supplies because the confirmation process regarding drug demand to the distributor must check the availability at the distributor as well as errors in writing supplies on the stock card and errors in recording drug supply data, so it is necessary to use technology in the form of information systems to simplify the request process and monitoring by leaders using a Supply Chain Management approach that is able to coordinate supply from several parts such as retail, distributors and consumers in order to stabilize retail inventory. The results of functionality testing get a percentage of 98.46%, and the results of usability testing get a percentage of 98.33%